The External Dimension of the Ubuntu Concept - SHUBIN Vladimir Gennadievich (Ученые записки Института Африки Российской академии наук, 2024)
The article explores the concept of “Ubuntu.” This term is more familiar to the general public not as a philosophical concept but as the name of the open-source operating system developed by Mark Shuttleworth, a South African by origin. It was no accident that he used this term for his system, which was distributed free of charge, since in a number of South African languages, the word “ubuntu” means “humanness,” “humanity to others.”